(untitled) (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To sensitize authors and new researchers to produce a quality research manuscript. Methods: Review of experiences and challenges faced by scientifi c journal editors and new authors; and scientifi c writing guidelines and workshops. Results: Impatient submission of manuscript with inadequate understanding of authors’ guidelines. Strength of own research and scope of journal not matching; lack of minimum training on writing and submission; journal publication from professional organizations not in primary priority list because of its voluntary nature of work. Conclusions: Publishing depends on professional commitment, academic interest and need, personal career and institutional interest, and availability of specifi c biomedical publishers. Keywords: authors’ guideline, biomedical journal, publication